AE monitoring of reinforced concrete squat wall subjected to cyclic loading with information entropy-based analysis. (15th June 2018) - Zhang, Xinchen; Shan, Wenchen; Zhang, Zhongwen; Li, Bing
Highlights: AE monitoring of a RC squat wall under cyclic loading was conducted to study the cracking process and damage states. A novel AE signal analysis method based on information entropy theory was conducted and verified. A comparison between information entropy based analysis and traditional b-value analysis was conducted. Abstract: Reinforced concrete (RC) squat walls have been widely used to resist horizontal force given its high lateral stiffness and strength. In this research, the crack development process of squat wall under non-parallel cyclic loading was monitored using an acoustic emission (AE) technique. In addition, a novel AE signal analysis method based on information entropy was studied. The results show that the AE technique is effective in monitoring the crack process of the squat wall. A strong correlation between the result of basic AE parameters analysis and real cracking state is also determined. Furthermore, accumulated AE energy shows a good correlation with the accumulated hysteretic energy and the damage assessment based on RA-AF analysis indicates the shear cracks are the dominant crack mode. Information entropy-based analysis was conducted, and its feasibility in monitoring the development of main cracks was validated. A comparison between information entropy-based analysis and b-value analysis was conducted finally, which shows that the information entropy value is more sensitive and specific than Ib value.